A flexible approach for measuring author-level publishing performance - Simões, N. (2020)
We propose a framework to evaluate, in relative terms, author-level publishing performance. To that end we introduce the publishing performance index (PPI) and the publishing performance box (PPB), and discuss the associated publishing profiles. We illustrate our approach conducting an extensive empirical application covering 472 top economists and developing several robustness tests. Instead of using a pre-designed measure without lexibility to adjust to the circumstances of each specific case, our approach accommodates alternative evaluation criteria, as defined by the evaluators. Beyond this key characteristic, our approach has some other important advantages: (1) it is easy to apply; (2) it is sensitive to the full list of publications and citations; (3) it is able to include additional dimensions of scientific performance beyond papers and citations; (4) it is a high granularity measure, providing a complete ranking of the authors under analysis.